PREVALENCE OF DYSLIPIDEMIA AMONG PATIENTS OF POLYCYSTIC OVARIAN SYNDROME: A CROSS SECTIONAL ANALYTICAL STUDY - ZAFAR, SALEHA; Yasmin, Tabinda; Saeed, Rabia; ASLAM, JAVARIA; Rafiq, Tanzila; Bin Saad, Ammar (Pakistan Journal of Physiology, 2024)
Background: Polycystic ovarian disease is a genetically complicated condition, most prevalent in women of reproductive age group. It is strongly associated with obesity, dyslipidemias, and menstrual disorders. Objective of this study was to determine the prevalence of dyslipidemia in patients of polycystic ovarian syndrome (PCOS). Method: A cross-sectional analytical study was conducted at the Department of Gynaecology, Bahawal Victoria Hospital, Bahawalpur, from 1st Jan to 31st Dec 2021. All newly diagnosed patients of PCOS between the ages of 18 and 35 with a BMI <25 Kg/m2 were included in the study. Participants were divided into subgroups according to their age and BMI. The fasting lipid profile was measured through a blood sample taken from each patient after an overnight fast. Total cholesterol >200 mg/dL, LDL-C >130 mg/dL, Triglycerides >150 mg/dL, and HDL-C <40 mg/dL were labelled as dyslipidemia. Chi-square test was used to calculate and estimate the relative risk (RR) of any associations observed. Results: Among total 286 analysed patients of PCOS, mean age was 24.4±5.367 years and mean BMI was 21.01±1.912 Kg/m2. Sixty nine (24.13%) patients had dyslipidemia. Patients in the 18–27 age group and a BMI of 21–23 Kg/m2 were more likely to have dyslipidemia with PCOS, [RR 44.90; 95% CI (16.93, 119.04); p<0.001], and [RR 32.12; 95% CI (8.02, 128.61); p<0.001] respectively. Conclusion: Dyslipidemia is seen in 24.13% individuals with PCOS. Screening in routine is recommended. Pak J Physiol 2024;20(1):19-21